mmu-miR-145a-5p Accelerates Diabetic Wound Healing by Promoting Macrophage Polarization Toward the M2 Phenotype - Hao, Yanhui; Yang, Leilei; Liu, Ying; Ye, Yumeng; Wang, Jiayu; Yu, Chao; Yan, Hua; Xing, Yuan; Jia, Zhaoqian; Hu, Cuicui; Zuo, Hongyan; Li, Yang (Frontiers in Medicine, 2021)
Diabetic wounds are recalcitrant to healing. One of the important characteristics of diabetic trauma is impaired macrophage polarization with an excessive inflammatory response. Many studies have described the important regulatory roles of microRNAs (miRNAs) in macrophage differentiation and polarization. However, the differentially expressed miRNAs involved in wound healing and their effects on diabetic wounds remain to be further explored. In this study, we first identified differentially expressed miRNAs in the inflammation, tissue formation and reconstruction phases in wound healing using Illumina sequencing and RT-qPCR techniques. Thereafter, the expression of musculus (mmu)-miR-145a-5p (“miR-145a-5p” for short) in excisional wounds of diabetic mice was identified. Finally, expression of miR-145a-5p was measured to determine its effects on macrophage polarization in murine RAW 264.7 macrophage cells and wound healing in diabetic mice. We identified differentially expressed miRNAs at different stages of wound healing, ten of which were further confirmed by RT-qPCR. Expression of miR-145a-5p in diabetic wounds was downregulated during the tissue formation stage. Furthermore, we observed that miR-145a-5p blocked M1 macrophage polarization while promoting M2 phenotype activation in vitro. Administration of miR-145a-5p mimics during initiation of the repair phase significantly accelerated wound healing in db/db diabetic mice. In conclusion, our findings suggest that rectifying macrophage function using miR-145a-5p overexpression accelerates diabetic chronic wound healing.